PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM SYARIAH (Studi pada Perusahaan Sub Sektor Perdagangan Eceran di Bursa Efek Indonesia Tahun 2021-2022) - Amelia Safitri; Mohammad Orinaldi; Kurniyati Kurniyati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of financial ratios on stock returns of retail trading companies listed on the Indonesia Stock Exchange (BEI) during the 2021-2022 period in quarters I, II, III and IV, either partially or simultaneously. The financial ratios studied are: Current Ratio (CR), Return On Assets (ROA), Price to Book Value (PBV) and Price Earning Ratio (PER). The population in this study are retail trading companies listed on the Indonesia Stock Exchange (BEI) during the 2021-2022 period in quarters I, II, III and IV. The research sample was 15 retail trading companies obtained using purposive sampling technique. The data collection technique used is documentation. Data analysis method using multiple linear regression. The results of this research show that partially the CR and PBV variables have an effect on stock returns, while ROA and PER have no effect on stock returns. Simultaneously, the variables CR, ROA, PBV and PER influence stock returns. The results of the coefficient of determination test (Adjusted R2) obtained a value of 0.489, this shows that the variables CR, ROA, PBV and PER influence stock returns in retail trading companies listed on the Indonesia Stock Exchange (BEI) during the 2021-2022 period in the first quarter. , II, III and IV amounted to 48.9%.